Do tornadoes really twist? : questions and answers about tornadoes and hurricanes - Berger, Melvin; Berger, Gilda; Bond, Higgins (New York, NY : Scholastic Inc., 2000)
Provides answers to a variety of questions about tornadoes and hurricanes, including "Where do most tornadoes strike," and "How long do hurricanes last?"
Includes index.
G5
Keywords: Tornadoes -- Miscellanea -- Juvenile literature; Hurricanes -- Miscellanea -- Juvenile literature